The Perception of “Beautiful” Indonesian Women in The Eka Kurniawan’s Novel “Beauty is a Wound” - Alfi Thoyyibah; Dinanil Funun El Milal (University of Darussalam Gontor, 2023)
Literature is a manifestation of the existence of life in society. Literature as a means of cultural and social representation that describes gender relations. One of the literary criticisms, there is a view called feminism, namely the women's movement caused by the awareness that women have the same rights as men. This article aims to discuss or analyze perceptions or views about the expression 'beautiful' for Indonesian women in the novel